PENGARUH LINGKUNGAN KERJA, MOTIVASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. TUPAI ADYAMAS INDONESIA KABUPATEN BOYOLALI DI BOYOLALI - Gea, Yernijati; Puji Rahayu, Listyowati; Safitri, Unna Ria; Suryana, Alean Kistiani Hegy (EKOBIS, 2024)
The purpose of this study was to analyze the effect of 3 independent variables (partial) which are work environment, work motivation and work discipline on the dependent variable Y, namely work productivity and also to determine the effect together (simultaneously). And the participants of this study are some of the company's employees. Purposive sampling was used to select samples for research. 100 company workers in ready-made cloth factories who were enrolled in this study became the research sample. Questionnaire data in the form of a questionnaire is the type of data used. Multiple linear regression analysis is used in the analytical method. According to the results of the F test, all the company's independent variables X1, X2, X3 have a significant effect on the dependent variable Y. well, the t-test reveals that while the variables X2 (work motivation) and X3 (work discipline) have a significant impact on the Y variable (productivity work), while variable X1 (work environment) does not significantly affect productivity. The R-square value indicates a coefficient of determination of 0.650. This shows that the three independent variables, namely X1 (work environment), X2 (work motivation) and X3 (work discipline) can explain 65.0% of the dependent variable Y (work productivity), while the remaining 37.5% is explained by the factors outside the model.